Stability analysis and improvement evaluation on residual soil slope: building cracked and slope failure - Goh, J.R.; Mohd Fakhrurrazi, Ishak; Zaini, M.S.I.; Muhammad Farhan, Zolkepli (IOP Publishing, 2020)
A case study of the building and road utilities which was loading directly on the slope at IIUM, Kuantan campus was damaged due to slope failure and landslide. This research are conducted to investigate and analyze the soil properties and parameters which affected the stability of residual soil slope against failure by conducting a comprehensive laboratory testing and software analysis. The properties of soil are determined from several physical index tests and shear strength tests. Numerical simulation model from engineering software SLOPE/W were performed to show the stability analysis (Factor of Safety - FOS) of typical residual soil slope without reinforcement and new innovative design of slope with reinforcement. This paper presents two types of slope design which are single reinforcement load and combination reinforcement loads. Through this research it is proved that both single and combination reinforcement load can improve the soil properties and parameters of the residual soil slope. The new slope design successfully proved to produce positive results by achieving up to 82.49% of stability improvement (FOS) within the correct position of reinforcement load added at failure slip surface on the slope.